PERLAKUAN ZAT PENGATUR TUMBUH HORMAX PADA PERKECAMBAHAN DAN PERTUMBUHAN AWAL TANAMAN TEBU (Saccharum officinarum L.) - Bambang Wicaksono Hariyadi; Nurul Nurul Huda; Dicki Wahyudi (Universitas Panca Marga Probolinggo, 2018)
The average production of sugar is 2.26 million tons per year, while consumption is about 5.10 million tons per year. This iswhat causes the number of production and consumption of sugar shows a fairly high gap. Extensification approach in increasingsugar cane production to achieve sugar self sufficiency target is quite difficult to achieve, so intensification program is one of theefforts that can be done through evaluation and optimization phase of germination and plant growth with application of growthregulator (Fitohormon). If this is done then to obtain a sugar cane plant that has the productivity and optimal yield is likely to beachieved (Ahmad Khuluq and Ruly Hamida, 2014). The experiment was conducted at Experimental Garden of AgricultureFaculty, Merdeka University, April-June 2017. Using Randomized Block Design with 3 replications. and 8 doses of Hormaxgrowing growth regulator, among others: 0 ml/l water (Control); 1 ml/l water; 2 ml/l water; 3 ml/l water; 4 ml/l water; 5 ml/ lwater; 6 ml/l water; 7 ml/l water. In conclusion, the use of Hormax significantly affected the germination rate, the number ofleaves, the number of roots, the wet weight and the dry weight per cane plant. Increased dose of Hormax followed by an increasein all variables of sugar cane observation. The highest results were shown dose of Hormax 7 ml/l water), but statistically notsignificantly different from the treatment dose of Hormax 6 ml/l water) and dose of Hormax 5 ml/l water. It is recommended th atto assist the germination and early growth of sugar cane using a dose of Hormax 5 ml/l water.